Znaczenie sporu między „starym” i „nowym” kierunkiem oświaty ludowej w Republice Weimarskiej – wnioski dla andragogiki - Solarczyk-Szwec, Hanna (Wydawnictwo Naukowe UAM, 2012)
Socio-political transformations in Germany at the turn of the 60s and 70s in the 19th c. strengthened a belief in a signifi cant role of education in the consolidation of their achievements. During the Weimar Republic (1919-1933), favourable political and legal conditions were created for the development of a pluralistic system of popular education. An extensive practice of adult education enforced the fi rst institutional measures in the fi eld of its professionalisation and in giving it a scientific character. In this spirit, research and scientifi c discussions were initiated. In the activities took an active part educational and academic activists, promoting results of the scientifi c work in the periodical press and book publications. In the Weimar Republic, the discussion turned into a dispute between the “old” and the “new” directions in popular education, which I have made the subject of this analysis, and its aim – an indication of the signifi cance of this dispute for the development of German andragogy at that time and its consequences for the present.
The importance of a discourse between the “old” and the “new” directions in popular education in the Weimar Republic – applications for andragogy
Keywords: history of adult education; andragogy; adult education concepts; Germany